Antecedents of Behavioral Intention to Adopt Sharia Digital Services in ZISWAF Distribution - Hariyanto Hariyanto; Ririn Tri Ratnasari; Sulistya Rusgianto; Anwar Allah Pitchay (Faculty of Economic and Business, 2024)
Research Originality: Indonesia, the fourth-most populous country after India, China, and the USA, has the largest Muslim population in the world, with a population of 231 million Muslims, or almost 13% worldwide. The number of millennial Muslim generations is around 59.415 million, or 85 percent of the total number of millennials, making it a potential market. This paper contributes to the existing behavioral intention literature by focusing on the integration of Acceptance and Use of Technology 2 (UTAUT2), Diffusion of Innovation (DOI) theory, and Perceived Security (PS) theory towards sharia digital services.Research Objectives: This research examines the antecedents of behavioral intention to adopt sharia digital services in ZISWAF distribution among the millennial Muslim generation in Indonesia.Research Methods: This study used a quantitative approach with the Structural Equation Modeling (SEM) analysis method and involved 350 respondents in Indonesia. By adopting the theories of Theory of Acceptance and Use of Technology 2 (UTAUT2), Diffusion of Innovation (DOI) theory, and Perceived Security (PS).Empirical Results: The study results show that performance expectancy, habit, price value, and compatibility have a positive and significant effect on behavioral intention to adopt sharia digital services in ZISWAF distribution. Furthermore, the price value variable is the strongest predictor of behavioral intention to adopt sharia digital services in ZISWAF distribution.Implications: This research has important meaning for the Indonesian government, ZISWAF institutions, and application providers because it provides valuable insight into considering accelerating ZISWAF distribution among the millennial Muslim generation.JEL Classification: Z12, L31How to Cite:Hariyanto., Ratnasari, R. T., Rusgianto, S., & Pitchay, A. A. (2024). Antecedents of Behavioral Intention to Adopt Sharia Digital Services in ZISWAF Distribution. Etikonomi, 23(1), 109 – 128. https://doi.org/10.15408/etk.v23i1.33892.